Terpene Moiety Enhancement by Overexpression of Geranyl(geranyl) Diphosphate Synthase and Geraniol Synthase Elevates Monomeric and Dimeric Monoterpene Indole Alkaloids in Transgenic Catharanthus roseus - Kumar, Sarma R.; Shilpashree, H. B.; Nagegowda, Dinesh A. (Frontiers in Plant Science, 2018)
Catharanthus roseus is the sole source of two of the most important anticancer monoterpene indole alkaloids (MIAs), vinblastine and vincristine and their precursors, vindoline and catharanthine. The MIAs are produced from the condensation of precursors derived from indole and terpene secoiridoid pathways. It has been previously reported that the terpene moiety limits MIA biosynthesis in C. roseus. Here, to overcome this limitation and enhance MIAs levels in C. roseus, bifunctional geranyl(geranyl) diphosphate synthase [G(G)PPS] and geraniol synthase (GES) that provide precursors for early steps of terpene moiety (secologanin) formation, were overexpressed transiently by agroinfiltration and stably by Agrobacterium-mediated transformation. Overexpression of G(G)PPS and co-expression of G(G)PPS+GES significantly enhanced the accumulation of secologanin, which in turn elevated the levels of monomeric MIAs. Transgenic C. roseus plants exhibited increased levels of root alkaloid ajmalicine. The dimeric alkaloid vinblastine was enhanced only in G(G)PPS but not in G(G)PPS+GES transgenic lines that correlated with transcript levels of peroxidase-1 (PRX1) involved in coupling of vindoline and catharanthine into 3′,4′-anhydrovinblastine, the immediate precursor of vinblastine. Moreover, first generation (T1) lines exhibited comparable transcript and metabolite levels to that of T0 lines. In addition, transgenic lines displayed normal growth similar to wild-type plants indicating that the bifunctional G(G)PPS enhanced flux towards both primary and secondary metabolism. These results revealed that improved availability of early precursors for terpene moiety biosynthesis enhanced production of MIAs in C. roseus at the whole plant level. This is the first report demonstrating enhanced accumulation of monomeric and dimeric MIAs including root MIA ajmalicine in C. roseus through transgenic approaches.